Transient Receptor Potential Channels - Islam, Md. Shahidul (Advances in Experimental Medicine and Biology,, 2011)
Transient Receptor Potential Channels offers a unique blend of thoughtfully selected topics ranging from the structural biology of this fascinating group of ion channels to their emerging roles in human diseases. This single book covers TRP channels of yeasts, flies, fishes frogs and humans. And from the biophysics of primary thermo-sensory events in cells to the thermosensation at whole organism level, from physiology of pain to the development of pain-killers, from psychiatric illnesses to cancers, from skin cells to sperms, from taste buds to testes, from established facts to heated debates, this book contains something for every TRP enthusiasts, beginner and expert alike. It includes crucial background information, critical analysis of cutting edge research, and ideas and thoughts for numerous testable hypotheses. It also shows directions for future research in this highly dynamic field. It is a book readers will be just as eager to give to others as keep for themselves.